STATUS MERKURI PADA ALIRAN SUNGAI KRUENG SABEE, AKIBAT LIMBAH PENGOLAHAN EMAS DI KABUPATEN ACEH JAYA - Iwandikasyah Putra; Sufardi Sufardi; Teuku Alvisyahrin; Amda Resdiar (Universitas Teuku Umar, 2021)
Gold mining activities in Aceh Jaya District could lead to mercury contamination of the environment.This research was conducted to assess the status of mercury in Krueng Sabee river as impacted bygold processing waste dumped into the river in the District of Aceh Jaya. Water, sediment, andaquatic animal (biota) samples were taken at three locations along the river, i.e. downstream, half-waycenter, and upstream. Mercury concentrations in the samples were analyzed by using SNI 02-0086-2005 method for sediment and biota, and SNI 01-3554-2006 method for water, and measured usingAtomic Absorption Spectrophotometer (AAS). The results were then compared to water qualitystandards for mercury Indonesian Govermental Regulation (KepMenLH No.02/ MenKLH/ 2002, PP.No. 18 Tahun 1999, dan BPOM No. 3725/ B/ SK/ VII/ 1989). The results showed that mercury levelsin Krueng Sabee river at all locations sampled during wet and dry seasons were below that of thewater quality standards, whereas mercury concentrations in sediment and biota samples at allsampling locations in Krueng Sabee river were above the maximum contaminant level. High levelsof mercury in the aquatic environment may pose a health concern for the community living in thecontaminated area.